Efektivitas Massage Effleurage Terhadap Penurunan Nyeri Pada Ibu Bersalin Kala I Fase Aktif Di UPT Puskesmas Ciruas Kabupaten Serang - Indah Nurfazriah (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2022)
About 90% of mothers giving birth are always accompanied by pain, while pain during labor is a common thing. Physiological events during labor can traumatize the mother because of the pain she experiences. Some mothers are even traumatized to get pregnant and give birth again because they are afraid they will experience the same pain. Severe pain during labor causes the mother to experience psychological disorders.The research design is a research using a quantitative approach. The research design used in this study was a quasi-experimental with two group pretest-posttest design with a sample of 36 pregnant women divided into 2 control groups 18 interventions 18 and the researchers selected respondents using purposive sampling technique. The average value of pain intensity without intervention in the control group was 6, while in the intervention group it decreased with an average of 3.5. There is an effectiveness of the influence of effleurage massage on reducing pain in mothers giving birth at the UPT Ciruas Health Center. It is suggested that the results of this study can add insight in digging information on the effectiveness and influence of massage effleuage on the pain level of women in childbirth during an active phase as part of a management of complementary midwifery care and traditional health which makes culture in Indonesia and the world.